PENINGKATAN HASIL BELAJAR IPA TENTANG MATERI SIFAT-SIFAT CAHAYA MELALUI METODE DISCOVERY LEARNING - Istidah, Anik; Suherman, Usep; Holik, Abdul (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2022)
This action research is motivated by the existence of a learning model that is used less varied, in the teaching and learning process, the teacher has not been able to create active and fun learning, so that students experience boredom during the learning process and students play less active roles, students still like to play alone while learning, so that student learning outcomes do not reach KKM. This research was conducted in two cycles. In each cycle, learning activities were carried out by applying the Discovery Learning method. The research subjects were fourth grade students consisting of 34 students. This study shows that student learning outcomes in the material of the properties of light through the Discovery Learning method can improve. The increase can be seen from the results of class action research in cycles I and II. In cycle I students who completed the KKM were 10 students or 29.41%. In cycle II, the number of students who completed the KKM was 30 students or 88.23%, an increase of 58.82% from cycle I. Thus, it can be concluded that the use of the Discovery Learning method can improve the learning process. Thus it can be concluded that the use of the Discovery Learning method can improve the learning outcomes of science material on the properties of light in class IV students of MI Daarul Qolam, Margahayu District, Bandung Regency in the 2020/2021 school year.ABSTRAKPenelitian Tindakan ini dilatarbelakangi oleh adanya model pembelajaran yang digunakan kurang bervariasi, dalam proses belajar mengajar, guru belum mampu menciptakan pembelajaran yang aktif dan menyenangkan, sehingga siswa mengalami kejenuhan selama proses pembelajaran dan siswa kurang berperan aktif, siswa masih suka bermain sendiri saat belajar, sehingga hasil belajar siswa tidak mencapai KKM. Penelitian ini dilaksanakan dalam dua siklus. Dalam tiap siklusnya dilaksanakan kegiatan pembelajaran dengan menerapkan metode Discovery Learning. Subjek penelitian yaitu siswa kelas IV terdiri dari 34 siswa. Penelitian ini menunjukan bahwa hasil belajar siswa dalam materi sifat-sifat cahaya melalui metode Discovery Learning dapat meningkat. Peningkatan tersebut dapat dilihat dari hasil penelitian tindakan kelas pada siklus I dan II. Pada siklus I siswa yang tuntas KKM sebanyak 10 siswa atau 29,41%. Pada siklus II siswa yang tuntas KKM sebanyak 30 siswa atau 88,23% meningkat 58,82% dari siklus I. Dengan demikian dapat disimpulkan bahwa penggunaan metode pembelajaran Discovery Learning dapat meningkatkan hasil belajar IPA materi sifat-sifat cahaya pada siswa kelas IV MI Daarul Qolam Kecamatan Margahayu Kabupaten Bandung tahun pelajaran 2020/2021.